Lactose-Induced Chronic Diarrhea Results From Abnormal Luminal Microbial Fermentation and Disorder of Ion Transport in the Colon - Xue, Hong; Zhang, Min; Ma, Jinxin; Chen, Ting; Wang, Fengyun; Tang, Xudong (Frontiers in Physiology, 2020)
Diarrhea is one of the major abdominal symptoms in lactose-intolerant subjects. The changes in the large intestinal luminal environment and disorder of the epithelial ion transport in lactose-induced diarrhea remain unclear. The present study aimed to investigate the effect of an incremental high-lactose diet (IHLD, 30%/40%/50%) on luminal microbiota, microbiota-derived metabolite concentrations and colonic ion transport. Gut microbiota were analyzed by 16S rRNA amplicon sequencing and the concentration of SCFAs by gas chromatography, galactose, lactose and lactic acid through assay kit; Ussing chamber was performed to detect basal and stimulated ion transport; The expression and location of SCFA transporters, the Na-H exchanger 3(NHE3), cystic fibrosis transporter regulater (CFTR) and NKCC1 in the colon mucosa were analyzed by western and immunostaining. The concentrations of lactose, galactose and lactic acid of the cecal content were markedly increased (P < 0.01) and SCFA concentration was significantly decreased (P < 0.01). This was associated with depletion of the Lachnospiraceae NK4A136 group and Ruminococcaceae UCG-005 and increased relative abundance of Lactobacillus, escherichia-shigella and megamonas in the cecal microbiota. The expression of monocarboxylate transporter 1 was decreased in the colonic mucosa of the IHLD group. Low NHE3 expression and phosphorylation levels, and decreases in delta basal short circuit current after apical Na+ removal in the colonic mucosa of the IHLD group contributed to Na+ accumulation in the lumen and decrease stimulated Cl- secretion with low CFTR and NKCC1 expression would compensate for water and electrolyte loss during the diarrhea process. These results indicated that the persistence of the diarrhea state was maintained by abnormal colonic microbiota fermentation leading to high concentrations of lactose, galactose and lactic acid and low SCFAs in the lumen, and decreased Na+ absorption with the low NHE3 expression and phosphorylation levels.